2020
DOI: 10.14814/phy2.14375
|View full text |Cite
|
Sign up to set email alerts
|

Assessing lymphatic route of CSF outflow and peripheral lymphatic contractile activity during head‐down tilt using near‐infrared fluorescence imaging

Abstract: Evidence overwhelmingly suggests that the lymphatics play a critical role in the clearance of cerebrospinal fluid (CSF) from the cranial space. Impairment of CSF outflow into the lymphatics is associated with a number of pathological conditions including spaceflight‐associated neuro‐ocular syndrome (SANS), a problem that limits long‐duration spaceflight. We used near‐infrared fluorescence lymphatic imaging (NIRFLI) to dynamically visualize the deep lymphatic drainage pathways shared by CSF outflow and disrupte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…To date, we have not imaged dermal backflow in the external lymphatics of treatment-naive HNC patients with known or suspected LN metastases, probably because these external lymphatics are typically not in the same lymphatic watershed directly draining interior oropharynx, larynx, and oral cancers. However, in preliminary studies of internal lymphatic drainage of treatment-naive HNC patients, few exhibited drainage into the lympho-jugular chain after mucosal administration of ICG [29], as was seen in normal-health subjects (Figure 4 above) [27]. This observation is preliminary and needs more carefully controlled studies to underscore changes in internal lymphatic drainage from the cranium with head and neck cancer progression.…”
Section: The Role Of Lymph Node Dissection and Rt On Lymphatic Functionmentioning
confidence: 91%
See 3 more Smart Citations
“…To date, we have not imaged dermal backflow in the external lymphatics of treatment-naive HNC patients with known or suspected LN metastases, probably because these external lymphatics are typically not in the same lymphatic watershed directly draining interior oropharynx, larynx, and oral cancers. However, in preliminary studies of internal lymphatic drainage of treatment-naive HNC patients, few exhibited drainage into the lympho-jugular chain after mucosal administration of ICG [29], as was seen in normal-health subjects (Figure 4 above) [27]. This observation is preliminary and needs more carefully controlled studies to underscore changes in internal lymphatic drainage from the cranium with head and neck cancer progression.…”
Section: The Role Of Lymph Node Dissection and Rt On Lymphatic Functionmentioning
confidence: 91%
“…Instead, intrathecal injections of Gd-contrast in humans and of ICG in animals show that cervical lymphatics are the major conduits of CSF outflow [25,26]. In humans, the possible neurological consequences of Gd deposits in the brain limit its use for assessing CSF outflow [27]. While intrathecal ICG administration has not been cleared by the FDA, we have conducted off-label administration of ICG into the mucosal lymphatics of the palatine tonsils under FDA clearance [26,28].…”
Section: Anatomy and Function Of Cranial/cervical Lymphaticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Salerni et al 19 reported a mathematical model of fluid flow in the eyes and brain which predicted increased ICP and IOP in microgravity, as well as decreased ocular blood flow in the choroid and ciliary body. As noted above, the lymphatic system has been proposed to play a role in contributing to SANS, and Rasmussen et al 32 described a technique that could be used to further our understanding of this. The authors reported subdermal indocyanine green (ICG) injections with near infrared fluorescent lymphatic imaging to visualize deep lymphatic outflow shared by CSF and in a small group of healthy human volunteers showed its disruption during HDT.…”
Section: Technology For Studying Sansmentioning
confidence: 99%